Legal and shari'a governance framework for sukuk issuance in the kingdom of Saudi Arabia a comparative analytical study - الأطر القانونية والشرعية للصكوك في السعودية - Alnaggar, Ahmed Mohamed Hassan; Othman, Anwar Hasan Abdullah (European Academy of Finance and Islamic Economics (EAFIE), 2019)
Saudi Arabia holds the second place globally after Malaysia, and the first place among the Arabic nations in the value of sukuk issuances with a total issuances of $ 117.8 billion (for the period 2001-2018), as the Kingdom aims in its vision to develop the financial sector (under Vision 2030), it played a major role in the development of the sukuk market . This will require an in-depth and up-to-date analysis of the applicable rules and regulations and the readiness of the regulatory and legal structure and Shari'a governance frameworks to achieve this goal .The research uses the comparative and descriptive approach to analyze relevant legal and regulatory texts, with a comparative study on these texts in Malaysia and the United Arab Emirates as Benchmark countries as they rank in the top global sukuk market in terms of the value issued, as well as hold a good track record in sukuk issuances and different structures . This will help to give a detailed and up-to-date picture of the legal framework governing the issuance of sukuk in Saudi Arabia .Through this comparative analysis, the research found several challenges at the level of legal and Shari'a governance framework for sukuk issuance in the Kingdom, which calls for several initiatives to address these challenges.